Incest and influence: The Private Life of Bourgeois England. Adam Kuper - Millán, Saúl (Alteridades, 2018)
Reseña del libro de Adam Kuper, Incest and Influence: The Privete Life of Bourgeois England, Harvard University Press, England, 2009.